KELEKATAN IBU DAN BAYI PASCAMELAHIRKAN PADA IBU YANG BEKERJA DITINJAU DARI MATERNAL SENSITIVITY - Arini Faizati; Resnia Novitasari (Universitas Islam Bandung, 2019)
Attachment is one of the important aspects in children’s development. However, there were some issues related with the condition of being working mothers. Based on that, the purpose of this study was to examine the relationship between the maternal sensitivity and the postnatal attachment. Respondents in the study is a working mother who have infants (0-24 months) and the number were 100 mothers. The hypothesis of this study assumed that there was a positive correlation between maternal sensitivity to postnatal attachment among working mothers. The instruments of this study were consisted of the Maternal Postnatal Attachment Scale (MPAS) (Condon & Corkindale, 1998) and Maternal Sensitivity Scale compiled by researchers in establishing maternal sensitivity aspect of Ainsworth (1969; 2006). The results showed that the research hypothesis was accepted, that was indicated with significant correlation between maternal sensitivity and postnatal attachment (r = 0.596; p = 0.000). This finding will be discussed further in this paper.